One year of treatment with elexacaftor/tezacaftor/ivacaftor in patients with cystic fibrosis homozygous for the F508del mutation causes a significant increase in liver biochemical indexes - Castaldo, Alice; Gelzo, Monica; Iacotucci, Paola; Longobardi, Annalisa; Taccetti, Giovanni; Terlizzi, Vito; Carnovale, Vincenzo (Frontiers in Molecular Biosciences, 2024)
Modulators of cystic fibrosis transmembrane conductance regulator (CFTR) mutated protein significantly improved the outcome of CF patients. We describe 63 patients followed independently in two CF Regional Centre (i.e., Campania and Tuscany regions), all homozygous for F508del mutation, treated for three years with Lumacaftor/Ivacaftor (LI) and thus, for one year with Elexacaftor/Tezacaftor/Ivacaftor (ETI). We studied biochemical parameters of liver damage and cholesterol metabolism. Beyond the improvement of BMI and lung function with LI treatment and even more with ETI, we found that the three years of LI treatment significantly improved liver function parameters (total and conjugated bilirubin, ALT, AP and GGT), while the subsequent ETI treatment causes significant increase of such parameters. We confirm that the treatment with LI does not correct hypocholesterolemia, whereas ETI treatment significantly did increase serum cholesterol. Such increase is likely due to the enhanced de novo biosynthesis, as indicated by the significant increase of serum lathosterol and likely, the subsequent liver cholesterol accumulation may contribute to trigger inflammation and worsen liver biochemical indexes. The increase of serum bilirubin and ALT, that we observed in about 94% and 84% of patients treated with ETI, respectively, suggests to further investigate the impact of ETI therapy on liver function indexes.